2018
DOI: 10.1186/s12864-018-5297-2
|View full text |Cite
|
Sign up to set email alerts
|

First genome-wide CNV mapping in FELIS CATUS using next generation sequencing data

Abstract: BackgroundCopy Number Variations (CNVs) have becoming very significant variants, representing a major source of genomic variation. CNVs involvement in phenotypic expression and different diseases has been widely demonstrated in humans as well as in many domestic animals. However, genome wide investigation on these structural variations is still missing in Felis catus. The present work is the first CNV mapping from a large data set of Next Generation Sequencing (NGS) data in the domestic cat, performed within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…Besides somatic-CNVs affecting neoplastic cells, normal cells also have variations in the number of copies, representing a source of genomic diversification during evolution 120,121 . Those mutations usually affect smaller genomic regions than somatic-CNVs and some of them-usually referred to as germline-CNVs-are implicated in cancer inheritance 15,16,[122][123][124] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides somatic-CNVs affecting neoplastic cells, normal cells also have variations in the number of copies, representing a source of genomic diversification during evolution 120,121 . Those mutations usually affect smaller genomic regions than somatic-CNVs and some of them-usually referred to as germline-CNVs-are implicated in cancer inheritance 15,16,[122][123][124] .…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, there is only one publication characterising CNVs in cats according to different breeds (Genova et al 121 ), and none characterising germline-CNVs associated with FMCs predisposition. When comparing our data with those of Genova et al, we observed that none of the animals in that study carried CNGs affecting B4 1-29 Mb and F2 64-82.3 Mb-enriched with cancer-related genes and significantly associated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of WGS for CNV detection is highly encouraged, because it overcomes many of the shortcomings of the other CNV detection methods such as the ones using array CGH and SNP data [18][19][20]. Genome-wide studies to discover CNV have already been done in other domesticated species, such as in Sus scrofa [49], Bos taurus [37,50] and Felis catus [38]. Here we provide a first glimpse of the goat genome CNV map at a dense genome coverage, using animals from 34 diverse breeds from the African continent.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been carried out to detect CNV using WGS data in various domesticated species: cattle [37], cats [38], chickens [39], dogs [40], etc. So far, there is no report of goat CNV discoveries using WGS data.…”
Section: Introductionmentioning
confidence: 99%